Nordic agriculture under climate change: A systematic review of challenges, opportunities and adaptation strategies for crop production - Wiréhn, Lotten (Land use policy, 2018)
•A systematic literature review of Nordic agriculture under climate change.•Presents a synthesis of complex interlinkages of challenges and opportunities.•Shows that potential adaptation actions involve important trade-offs.•Identifies a knowledge gap regarding such adaptation-induced trade-offs. The Nordic countries’ agricultural sector is potentially considered both a winner and loser in relation to climate change. With effective adaptation management, climate change could lead to increased agricultural productivity. Yet if concurrent challenges are left unaddressed, productivity losses may impede gains. Thus, adaptation to climate change is key both to avoid negative consequences and to benefit from opportunities. This paper conducts the first systematic literature review of scientific and grey literature on climate change related opportunities and challenges in Nordic agriculture, resulting in a complex overview of required adaptation actions. The synthesis on suggested adaptation policies and measures shows that farm based adaptation measures appear to be more abundant and more discussed than policy driven adaptation in the scientific literature. This paper identifies a knowledge gap regarding the complexity of adaptation needs and trade-offs in the Nordic agricultural sector. In conclusion, although the agricultural sector in the Nordic region is facing certain benefits from climate change, this review demonstrates profound challenges related directly to climate change. The synthesis of suggested adaptation actions furthermore indicates that adaptation involve trade-offs, however, increased knowledge on this subject is required. Failing to address these challenges might impede Nordic agriculture’s potential gains from climate change in a long-term perspective.